Crystallization Modulation and Holistic Passivation Enables Efficient Two-Terminal Perovskite/CuIn(Ga)Se2 Tandem Solar Cells - Geng, Cong; Zhang, Kuanxiang; Wang, Changhua; Wu, Chung Hsien; Jiang, Jiwen; Long, Fei; Han, Liyuan; Han, Qifeng; Cheng, Yi‑Bing; Peng, Yong (Nano-Micro Letters, 2024)
Two-terminal (2-T) perovskite (PVK)/CuIn(Ga)Se2 (CIGS) tandem solar cells (TSCs) have been considered as an ideal tandem cell because of their best bandgap matching regarding to Shockley–Queisser (S–Q) limits. However, the nature of the irregular rough morphology of commercial CIGS prevents people from improving tandem device performances. In this paper, D-homoserine lactone hydrochloride is proven to improve coverage of PVK materials on irregular rough CIGS surfaces and also passivate bulk defects by modulating the growth of PVK crystals. In addition, the minority carriers near the PVK/C60 interface and the incompletely passivated trap states caused interface recombination. A surface reconstruction with 2-thiopheneethylammonium iodide and N,N-dimethylformamide assisted passivates the defect sites located at the surface and grain boundaries. Meanwhile, LiF is used to create this field effect, repelling hole carriers away from the PVK and C60 interface and thus reducing recombination. As a result, a 2-T PVK/CIGS tandem yielded a power conversion efficiency of 24.6% (0.16 cm2), one of the highest results for 2-T PVK/CIGS TSCs to our knowledge. This validation underscores the potential of our methodology in achieving superior performance in PVK/CIGS tandem solar cells. Highlights: 1 Integrating perovskite solar cells onto irregular rough CuIn(Ga)Se2 (CIGS) surfaces remains a challenge; new strategy was explored to develop monolithic perovskite/CIGS tandem solar cell by manipulating the crystallization of perovskite. 2 Surface reconstruction and field-effect passivation are developed synergistically to issue complex interface relationship between perovskite and C60. 3 The champion power conversion efficiency （PCE） of 24.6% realized, providing significant commercial opportunities for all thin-film-based perovskite/CIGS tandem cells.